If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 6 = 18 Reorder the terms: 6 + 2a = 18 Solving 6 + 2a = 18 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2a = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 2a = 18 + -6 2a = 18 + -6 Combine like terms: 18 + -6 = 12 2a = 12 Divide each side by '2'. a = 6 Simplifying a = 6
| -5(t-4)-(t+4)=9 | | 1/16x=11/3 | | 64x+25=66 | | 25x^4-16x^2=0 | | 6+3(x-4)=10-4(x-6) | | 64x+25+25=66 | | (15/7)=(1/14)X | | 3x+160y=180 | | 3x^3-2x^2+1=0 | | 5(k-2)-5=5k-(4k-2) | | y+(x+20)=180 | | 9x^2/3-26x^1/3-3=0 | | 3x-(7x+4)=9-4x | | 3.50+(125x)=12 | | 3a-3=8(a+1)+11a+7 | | (2*x^2)-(7*x)-(8)=0 | | (1-x)*(3x-2)= | | 12x^2y^3+36x^4-72x^3y^2=0 | | 7/2x-3/2=53/2 | | 9.9x+41.04=-10.1x+40.28 | | 3.50+125x=12 | | 9.9x+41.04=10.1x+40.28 | | (x+5)(x-2)=2(x-2)-18 | | 6.2x-3.6=2.6 | | -(z+7)+(2z+1)=-4(z+1) | | x+6+2x-3=90+45 | | 24x^2y^3+36x^4-72x^3y^2=0 | | 22y+18-15y= | | 5(3z-1)-2(z+2)=8(z+1) | | 4n+7-2n=3n-3 | | 60x=50(x+1) | | 2x^2-16x=7 |